The Impact of Human Resource Management in Amhara Regional State on the Development of Sport in Ethiopia - Daniel Getnet Admit (Journal Research of Social Science, Economics, and Management, 2023)
Sport experts' management can be described as a strategic, integrated, and coherent approach to the employment, development, and well-being of the people working in organizations. It has a strong conceptual basis drawn from the behavioral sciences and strategic management, and human capital theories. Little is known about the impact of sport experts' management on the development of sport. Therefore, this study intended to scrutinize the impact of sport expert's management on the development of sport in Amhara national regional state, Ethiopia. To achieve the stated purpose, correlational study. Data was collected from 108 sports experts through 55 questionnaires. Percent, reliability, Kolmogorov-Smirnov test, correlation, and linear regression by SPSS version 23 were used for data entry and analysis at 0.05 level. The results show that sports experts' management practices, ESH (r, .380, .001); EWC (r .411, .000); EPA (r. 502, .000); EMS (r, .638, .000), and ETS (r, .505, .000) have significant positive associations to the development of sport, respectively. Moreover, the sport expert's management has a46.2 % impaction the development of sport. EWC (B. 126, .000) and EMS (B= .616, .000) show significant positive predictions. Therefore, it can conclude that the sport expert's management has an appositive and moderate to large association and 46.2% impaction the development of sport. Furthermore, the researchers recommend that the office should design and exercise a sound human resource management structure that helps the development of sport.